STRATEGIES FOR EFFECTIVE POLICY IMPLEMENTATION IN NIGERIA: A CASE OF FEDERAL CHARACTER PRINCIPLE (Journal of Governance and Development (JGD), 2024)
The implementation of policies by the government appears to be ineffective in using the Federal Character Principle (FCP) as a case study. The FCP, which was enacted to guarantee the distribution of employment in Nigeria’s public service, appears to not be achieving its goal as the disparity in the distribution of employment remains inherent in the civil service. Disparity perfectly describes the distribution of employment in the Nigerian civil service, regardless of the enactment of the FCP. Subsequently, this paper endeavours to investigate techniques that would guarantee the viable implementation of the FCP in Nigeria’s civil service. The paper sourced its data from secondary sources and relevant documents. The paper revealed that strategies that can ensure the FCP can be effectively implemented include the application of a Tribunal, the inclusion of civil society in the implementation of the enabling laws and ensuring that officers of the commission are not appointed based on party affiliation. The paper recommends that sanctions should be used for defaulters of the policy.